International trade forum - International Trade Centre (Geneva International Trade Centre, 1995)
​International Trade Forum focuses on trade promotion and export development as part of ITC’s technical Co-operation programme with developing countries and economies in transition
​Published quarterly since 1964 in English, French and Spanish, The library has only the Eng Edition.
Keywords: International Trade; TRADE PROMOTION; EXPORT DEVELOPMENT; INTERNATIONAL TRADE; DEVELOPING COUNTRIES; PERIODICALS